Exploring the potential of some natural indoles as antiviral agents: quantum chemical analysis, inverse molecular docking, and affinity calculations - Belal, Amany; Abdou, Aly; Miski, Samar F.; Ali, Mohamed A. M.; Ghamry, Heba I.; Obaidullah, Ahmad J.; Zaky, Mohamed Y.; Hassan, Ahmed H. E.; Roh, Eun Joo; Al-Karmalawy, Ahmed A.; Ibrahim, Mona H. (Frontiers in Chemistry, 2025)
Human immunodeficiency virus (HIV) and hepatitis C virus (HCV) infections represent critical global health challenges due to the high morbidity and mortality associated with co-infections. HIV, the causative agent of acquired immunodeficiency syndrome (AIDS), infects 4,000 people daily, potentially leading to 1.2 million new cases by 2025, while HCV chronically affects 58 million people, causing cirrhosis and hepatocellular carcinoma. Indole-based compounds play a crucial role in antiviral drug development due to their “privileged scaffold” structure. This study investigates the antiviral potential of natural indoles, gardflorine A–C, derived from Gardneria multiflora Makino, a plant traditionally used to treat various ailments. We employed molecular docking, ADMET analysis, and computational techniques [frontier molecular orbital (FMO), natural bond orbital (NBO), and density functional theory (DFT)] to evaluate these compounds” potential as multi-target antiviral agents against HIV and HCV proteins.